Antibacterial Activity of Chlorophyta, Phaeophyta, and Rhodophyta Using Various Antibiotics as Positive Controls: A Systematic Review and Meta-Analysis - Aisah, Aisah; Suyatma, Nugraha Edhi; Kusumaningrum, Harsi Dewantari (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Different species of marine macroalgae have been reported to demonstrate antimicrobial activities against numerous bacteria, with varying results. According to the studies, other antibiotics have been used as positive controls. This study evaluated the effect of crude extracts and sulphated polysaccharides from Chlorophyta, Phaeophyta, and Rhodophyta in inhibiting bacterial growth in terms of the diameter of inhibition zones (DIZ) using a systematic review and meta-analysis approach. A total of 835 data, extracted from 23 selected articles, were analyzed using OpenMeesoftware by comparing the standardized mean difference (SMD) and 95% confidence interval (CI). The largest DIZ that Chlorophyta showed was 35 mm, Phaeophyta was 27.3 mm, and Rhodophyta was 25.66 mm, which was categorized as a very strong activity. The crude extract revealed a better inhibitory activity than the sulphatedpolysaccharides. The overall effect size for crude extracts was with SMD = -1.72 (CI = -1.96 to -1.48, I2 = 84.65%, p 0.000) and for sulphated polysaccharides with SMD = -13.07 (CI = -16.00 to -10.14, I2 = 85.8%, p 0.000), respectively. Subgroup analysis showed that when ciprofloxacin was used, the SMD value was -12.88 (CI = -14.50 to -11.25), whereas if ampicillin was used, the SMD value was 1.81 (CI = 1.27 to 2.35). This study proved that Chlorophyta, Phaeophyta, and Rhodophyta revealed promising antibacterial activities. However, the overall effect size was affectedby the antibiotic used when comparing the SMD of the DIZ using a meta-analysis approach. Other factors, such as extraction methods and bacterial strains that likely affect the overall effect size, are subjected to further analysis in the next study.